ANALISIS HUBUNGAN ANTARA UMUR, BEBAN KERJA KELELAHAN KERJA DAN MOTIVASI KERJA DENGAN STRES KERJA PERAWAT di RSUD MANEMBO-NEMBO BITUNG - Rengkung, Chrisal Novri Jozef; Kairupan, Bernabas Harold Ralph (JURNAL KEPERAWATAN, 2023)
Background: Work stress has become a global issue that affects all professions, including health care workers, both in developed and developing countries. The high workload, work fatigue and work motivation experienced by nurses can increase the level of stress in the workplace. Objective: This study aims to analyze the relationship between age, workload, work fatigue and work motivation with the work stress of nurses at RSUD Manembo-Nembo Bitung. Methods: The population of this study included all nurses at RSUD Manembo-Nembo Hospital Bitung, totaling 189 with the research sample using a total sampling technique, thus the total sample was 189 (21 men; 168 women). The research data was obtained by administering a set questionnaire that measured each variable (age, workload, work fatigue, work motivation, and work stress). Univariate, bivariate, and multivariate analyses were used in data analysis. Result: This study found that there was a significantly positive relationship between age and work stress, workload and work stress, and work fatigue and work stress. However, the research results show that work motivation and work stress have a significantly negative relationship. ). Conclusion: There is a significant relationship between workload, work fatigue, work motivation and stress on nurses at RSUD Manembo-Nembo Bitung. This study also found that work fatigue is the most dominant variable with work fatigue. Keywords: work stress; workload; work fatigue; work motivation